Collateral Circulation and Rabep2 Polymorphisms in Large Artery Occlusion: Impacts on Short‐ and Long‐Term Prognosis - Kun Zhang; Luji Liu; Tong Li; Rui Wang; Kailin Bu; Pandi Zhao; Xiaoyun Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Intracranial anterior circulation large artery occlusion (AC‐LAO) is a predominant cause of ischemic stroke. Although collateral circulation plays a critical role in stroke outcomes, the genetic and environmental factors affecting collateral development are not fully understood. This study aimed to elucidate the associations between Rabep2 gene polymorphisms, collateral circulation, and both short‐ and long‐term prognoses in patients with anterior circulation large artery occlusion. Methods and Results We recruited 449 patients with anterior circulation large artery occlusion with cerebral infarction. Collateral circulation was assessed using single‐phase computed tomography angiography, and stroke outcomes were evaluated at 1 month and 1 year using the modified Rankin Scale. A subset of 180 patients underwent genetic analysis for Rabep2 polymorphisms. Multivariable logistic regression was employed to identify predictors of short‐term and long‐term outcomes. Enhanced collateral circulation (P<0.001), lower high‐density lipoprotein levels (P=0.019), and the absence of complications (P<0.001) were significantly correlated with favorable short‐term outcomes. In the long term, age (P=0.039) and diabetes (P=0.006) were independent predictors of poor prognosis, whereas complications demonstrated a protective effect (P=0.016). The rs11645302 polymorphism of Rabep2 was linked to poorer collateral circulation among patients with the CC genotype (odds ratio [OR], 0.498 [95% CI, 0.270–0.918], P=0.025). Conclusions Collateral circulation, high‐density lipoprotein levels, Rabep2 gene polymorphisms, age, and diabetes are significant predictors of outcomes in patients with anterior circulation large artery occlusion. These findings underscore the potential to integrate genetic and vascular factors into personalized risk stratification and therapeutic strategies for ischemic stroke. Registration URL: https://www.ClinicalTrials.gov; Unique Identifier: NCT04091412.